Path-Constrained Data Gathering Scheme (Global Journal of Computer Science and Technology, 2013)
Several studies in recent years have considered the use of mobile elements for data gathering in wireless sensor networks so as to reduce the need for multi-hop forwarding among the sensor nodes and thereby prolong the network lifetime Since typically practical constraints preclude a mobile element from visiting all nodes in the sensor network the solution must involve a combination of a mobile element visiting a subset of the nodes cache points while other nodes communicate their data to the cache points wirelessly This leads to the optimization problem of minimizing the communication distance of the sensor nodes while keeping the tour length of the mobile element below a given constraint In this paper we investigate the problem of designing the mobile elements tours such that the length of each tour is below a per-determined length and the number of hops between the tours and the nodes not included in the tour is minimized To address this problem we present an algorithmic solution that consider the distribution of the nodes during the process of building the tours We compare the resulting performance of our algorithm with the best known comparable schemes in the literature